Forearc tectonics and volcanism during the Devonian–Carboniferous evolution of the North Patagonian segment, southern Chile (41,3°S) - Palape, C.; Quezada, P.; Bastías, J.; Hervé, F.; Reyes, T.; Veas, M.; Vildoso, F.; Calderón, M.; Theye, T.; Fuentes, F.; Chiaradia, M. (Frontiers in Earth Science, 2022)
Late Paleozoic to Early Mesozoic subduction complexes formed during the evolution of southwestern Gondwana and extensively crop out along the Chilean continental margin. Recent findings in northern Patagonia (40°-43°S) revealed that accretionary processes were active since the Devonian, when enhanced lithosphere stretching in the forearc led to the formation of Chaitenia island arc. The extension in the crust consecutively developed a backarc basin, which culminated during a compressive episode that re-amalgamated the Chaitenia island arc with the margin. This episode produced intermediate grade metamorphism in the sedimentary rocks that were formed throughout the extension. To constrain the tectonic evolution of these processes we combined petrology, structural analysis, whole-rock geochemical and whole-rock isotopic tracing (Sr-Nd-Pb) data along with thermodynamic modelling. Two petro-tectonic domains are here defined. The Western Coastal Range Domain is composed by Carboniferous to Permian metapsammopelitic rocks, which are mainly schists with a metasedimentary Carboniferous protolith exhibiting a penetrative northeast to southwest dipping main foliation associated to basal accretion. The Eastern Coastal Range Domain is comprised by garnet micaschists, metabasalts, metarhyolites and metasandstones. This unit is folded by three ductile structures, the first is related to rootless isoclinal folds, the second associated to a kilometric scale west-verging tight folds and the third to a west-verging cylindrical folds. The volcanic rocks of this domain are comprised by Middle Devonian alkaline metarhyolites and metabasalts with enriched-MORB and normal-MORB affinities. Trace element composition suggest that the metabasalts formed through shallow melting in an extensional setting over a supra-subduction zone. Nd and Pb isotope data points to a mantle source change for the basaltic melts from an EM1-like to a DM-like and are interpreted to reflect the embryonic to mature evolution of the early Devonian to Carboniferous backarc system. The calculated P-T evolution of the garnet micaschists follows: (i) a clockwise IP-IT prograde Barrovian path, (ii) an isobaric thermal increase at 7 kbar and 540°C and (iii) an adiabatic decompression. Finally, after the metamorphism, these rocks were uplifted by thrusting processes that probably occurred during the late Permian.